Penerapan asas kepastian hukum dan asas keadilan dalam sengketa kepailitan - Marisa, Nabila (Maliki Interdisciplinary Journal, 2024)
Bankruptcy is a condition in which a person or business entity is unable to complete the payment of its debts to creditors caused by obstacles, problems or others, so that it can be said to be bankrupt in the commercial court. There is a principle of legal certainty to determine the problems that occur in this bankruptcy dispute. So the understanding of the principle of legal certainty itself is a principle in a legal state that prioritizes legislation, propriety, and justice in every state administration policy. The requirements for a person to be declared bankrupt are contained in Article 2 paragraph (1) of Law No. 37 of 2004 concerning bankrupt and PKPU. In the context of bankruptcy law, "debtor" refers to a party who is experiencing financial difficulties and has outstanding debts. If the debtor cannot fulfill its debt payment obligations, then the court may decide to declare the debtor bankrupt. This article aims to determine the application of the Principle of Legal Certainty in bankruptcy disputes so that there is no abuse of authority.